Receptors P1 and P2 as Targets for Drug Therapy in Humans - Faria, Robson (IntechOpen, 2020)
This book aims to provide a brief update on the functions of purinergic receptors in various systems, in addition to the signaling pathway activated to mediate these functions. We address the influence of hypoxia by modulating the activity of these receptors under physiological and pathophysiological conditions. Additionally, we describe the mechanisms of induction of pain and inflammation in different systems. Finally, the book discusses some of the main bioinformatics tools currently used to improve or discover new prototypes capable of selectively acting on these receptors with estimated parameters of satisfactory solubility and toxicity for possible commercial implementation.